2021
DOI: 10.14740/gr1391
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Endoscopic Retrograde Cholangiopancreatography-Related Complications in Patients With Liver Transplant: A Meta-Analysis and Systematic Review

Abstract: Background: Existing literature on post-endoscopic retrograde cholangiopancreatography (ERCP) complications in patients with liver transplant remains scarce and largely inconsistent. We therefore aimed to systematically review and analyze the literature on complication rates associated with ERCP in patients with liver transplant. Methods:We performed a comprehensive literature search in Pub-Med, PubMed Central, Embase, and ScienceDirect databases from inception through March 2020 to identify all the studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Within our study, 16.1% of cases exhibited infections after ERCP, defined by the presence of fever and an increase in CRP levels leading to antibiotic therapy. Notably, this infection rate appears higher compared to other studies [5,19,23], which have reported infection rates ranging from 0.2% to 5% in liver transplant patients after ERCP. It is essential to acknowledge that the definition of infection after ERCP in the existing literature is highly inconsistent, limiting comparability in this domain.…”
Section: Discussioncontrasting
confidence: 67%
“…Within our study, 16.1% of cases exhibited infections after ERCP, defined by the presence of fever and an increase in CRP levels leading to antibiotic therapy. Notably, this infection rate appears higher compared to other studies [5,19,23], which have reported infection rates ranging from 0.2% to 5% in liver transplant patients after ERCP. It is essential to acknowledge that the definition of infection after ERCP in the existing literature is highly inconsistent, limiting comparability in this domain.…”
Section: Discussioncontrasting
confidence: 67%
“…A recent metaanalysis demonstrated that the pooled prevalence of bleeding, pancreatitis, and cholangitis among patients with cirrhosis undergoing ERCP was 5.1%, 3.02%, and 0.12%. 17 Similarly, Tarar et al 18 demonstrated that the risk of post-ERCP bleeding and pancreatitis, but not cholangitis, are significantly higher among patients with cirrhosis compared with non-cirrhotic counterparts.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, ERCPs are not without risks, with post-ERCP pancreatitis (PEP) as the most feared complication. A recent systematic review and meta-analysis has reported an incidence of PEP among LT recipients of 3.4% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, ERCPs are not without risks, with post‐ERCP pancreatitis (PEP) as the most feared complication. A recent systematic review and meta‐analysis has reported an incidence of PEP among LT recipients of 3.4% [10]. Less common complications after ERCP are postsphincterotomy hemorrhage and cholangitis, which occur in 1.1% and 0.8% of LT recipients, respectively [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation